CT Study of the Arytenoid Cartilage in Patients with Laryngeal Contact Granuloma. (December 2017) - Li, Jinrang; Tian, Shiyu; Zou, Shizhen; Wang, Qingjun; Tai, Xuhui; Chen, Xuesong
Objective: To explore high-resolution computed tomography (HRCT) characteristics of arytenoid cartilage in patients with laryngeal contact granuloma (LCG). Setting: Tertiary hospitals. Study Design: Individual case-control study. Methods: HRCT scans were obtained before treatment from 42 patients with LCG. Similar scans were obtained from 50 patients with glottic laryngeal cancer or vocal cord leukoplakia without vocal process involvement. Results: Forty-two male patients with LCG were enrolled in the study. There were 41 patients with unilateral vocal cord lesions, and 1 patient had bilateral lesions. All 50 eligible patients in the laryngeal lesion group were men. There were 39 patients with unilateral lesions, and 11 had bilateral lesions. The rate of arytenoid cartilage sclerosis in the LCG group was 79.07% (34/43) on the lesion side and 7.32% (3/41) on the healthy side. In the laryngeal lesion group, the rate of arytenoid cartilage sclerosis was 13.11% (8/61) on the lesion side and 2.56% (1/39) on the healthy side. The rate of arytenoid cartilage sclerosis on the lesion side of patients with LCG was significantly higher than on the healthy side of patients with LCG and significantly higher than both the healthy and lesion sides of patients with laryngeal lesions ( P < .001). Conclusions: Arytenoid cartilage sclerosis was observed on the lesion side in most patients with LCG, and the presence of sclerosis may support the diagnosis of LCG.